The Attendance System Using a Quick Response Code-based Website at SMK Negeri 1 Tinambung - Nugraha, Aidi (Universitas Nusantara PGRI Kediri, 2023)
SMK NEGERI 1 Tinambung is one of the vocational high schools in Polewali Mandar Regency that still employs a manual teacher attendance process. This research aims to implement a attendance system using a Quick Response Code-based Website at SMK Negeri 1 Tinambung, determine the system efficiency level, as well as assess user responses to the system. This is because the manual attendance process conducted by staff still exhibits deficiencies in recording and compiling attendance reports in a timely manner. The design of the attendance system using a Quick Response Code-based Website utilizes the PHP programming language with MySQL database processing. The implementation of this system employs a quantitative method to obtain data analysis by distributing questionnaires to respondents who have tried the system. The results of the quantitative research method indicate that the implementation of the attendance system using a Quick Response Code-based Website is suitable for implementation within the school environment due to its efficiency and positive response from teachers as users. Testing of the software system using the black box method also demonstrates the system's success in its application.